Balancing the Scales: The Role of Work-Life Balance and Technological Support in Enhancing Gig Worker Productivity in Indonesia - Parman, Parman; Shafar, Muhammad Uliah; Putri, Deasy Soraya A. Aminartha (UI Scholars Hub, 2025)
Research Aims: This study examined the impact of work-life balance (WLB) initiatives on gig worker productivity, focusing on the mediating role of job satisfaction and the moderating effects of gig work characteristics and technological support. Design/Methodology/Approach: PLS-SEM was used in this study to analyse survey data collected from a sample of 400 gig workers engaged in various platforms, including Gojek, Grab, Shopee, and Freelancer.com. The survey instrument comprised structured questions designed to measure key constructs, namely WLB initiatives, technological support, job satisfaction, and employee productivity. Research Findings: WLB initiatives significantly positively impacted employee productivity, with job satisfaction functioning as a key mediating factor in this relationship. Moreover, the effectiveness of WLB initiatives was further amplified under conditions of low work intensity, stable gig roles, and robust technological support. Theoretical Contribution/Originality: By applying the Job Demands-Resources (JD-R) model to the gig economy, this study highlighted the critical role of tailored interventions, specifically the integration of technological tools and effective workload management, in enhancing both productivity and job satisfaction among gig workers. Managerial Implication in the South East Asian Context: The findings underscored the necessity for culturally responsive WLB initiatives and enhanced technological support to address persistent challenges, including job insecurity and inconsistent workloads, within Southeast Asia’s evolving labour market. Research Limitation & Implications: The cross-sectional design of this study limited the ability to draw causal inferences, and the findings may not be fully generalisable beyond the Indonesian context. Future research should employ longitudinal designs and examine diverse cultural settings to refine and validate strategies aimed at promoting sustainable productivity and well-being among gig workers.